Imitation of Compensator and Adaptive Processes in Biosystems - Antomonov, M.Yu. (Cybernetics and computer engineering, 2020)
The purpose of the paper is to develop a formalized classification of adaptive processes types based on mathematical modeling of their dynamics. Results. The structurally functional model of the adaptive process is presented as three connected subsystems. The output process of the first subsystem is described by an exponential function with a constraint, of the second — a logistic (S-shaped) function, of the third — their difference, i.e. unimodal curve.The operation of such a system is considered for different ratios of the parameters of the transfer functions of the subsystems (conversion factors and time constants). It is proposed to use the output function of this system as an identifier of various types of adaptive reactions: adaptation, compensation, reparative regeneration and a pathological process. Criteria for definition of such a distinction are proposed using integral and dynamic characteristics of mathematical models. Метою статті є розроблення формалізованої класифікації типів адаптивних процесів на основі математичного моделювання їхньої динаміки. Результати. Структурно-функціональну модель адаптивного процесу подано у вигляді трьох підсистем. Вихідний процес першої підсистеми описується експоненціальною функцією з обмеженням, другої - логістичною (S-подібною) функцією, третьої - їхньою різницею, тобто унімодальною кривою.